The Impact of Economic Securityon Bank Deposits and Investment - Fabricius, Michael (IMF Working Papers; Working Paper, 1998)
This paper highlights the importance of institutions in explaining the variation of investment rates and of two measures of bank deposits across countries. A general index of economic security is created for 130 countries. Its explanatory power is compared with measures of specific institutional arrangements. For investment as well as for bank deposits, specific institutional factors are shown to be highly significant and outperform the general index.